Study and Follow-up of the Iraqi Railway System utilize GIS (The International Journal for Scientific Research, 2024)
In this project, the land transport system was monitored using the railways in Iraq, mapping the cities it passes through using geographic information systems, and clarifying the governorates that the railways do not pass through, and damaged or old railways that have not been updated from 2003-2024, the results were that there are five provinces that the railway has not passed through since it entered Iraq in the last century, which are (Najaf, Messan, Sulaymaniyah, Dohuk and Erbil ), there are also seven important railway lines starting from Baghdad that have been stopped since 2003, the Mosul-Qamishli line has stopped and a line from Mosul, to neighboring countries is suspended and all of them need maintenance and rehabilitation.
Keywords: Iraqi Railway; ArcGIS; government railway; land transport